Efektifitas Terapi Akupuntur Terhadap Keberhasilan Rehabiltasi Pasien Pasca Stroke: Literature Review - Galih Noor Alivian; Koernia Nanda Pratama (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Introduction : Stroke is a sudden attack that occurs in the brain involving blood vessels in the brain (clogged or ruptured) and eventually manifests in various symptoms (starting from paralysis, difficulty speaking / slurred, swallowing disorders, and so on). This disease is divided into ischemic-infarction stroke and hemorrhagic stroke. In Indonesia, this disease has increased from 7% to 10.9%. This indicates that stroke is a disease that is quite dangerous and requires appropriate treatment or rehabilitation.Method: The search for journal articles was conducted electronically using several databases, namely DOAJ, PubMed and Google Scholar with the keyword